Characterization of 2D Al2O3:C, Mg radiophotoluminescence films in charged particle beams. (February 2021) - De Saint-Hubert, Marijke; Castellano, Fabio; Leblans, Paul; Sterckx, Paul; Kodaira, Satoshi; Swakoń, Jan; de Freitas Nascimento, Luana
Abstract: In particle-therapy, 2D dosimetry systems require high spatial resolution and linear dose response as the patient treatment show steep gradients of dose in depth. In this work we report on the characterization of the radiophotoluminescence (RPL) response from Al₂O₃:C, Mg films exposed to proton (61.3 MeV, 91.5 MeV, 155.5 MeV and 230 MeV) and carbon clinical beams (110 MeV/u). The film response is evaluated in terms of properties particularly important for relative dose measurements, as dose response, film uniformity and minimum detectable dose. The films, based on coatings with average grain sizes of ≈7 μm, demonstrate a better response than those used in our previous studies, with grain sizes of ≈47 μm. Moreover, the Linear Energy Transfer (LET) changes when penetrating through material and it is known that solid-state detectors change luminescence efficiency η HT, γ as a function of LET. Therefore, we performed a detailed characterization of our new film to evaluate its response as function of dose and LET. The η HT, γ curve, as a function of particle LET, obtained from discrete dose points (slabs) η HT, γ is compared with the η HT, γ curves from Al₂O₃:C (OSL) and Al₂O₃:C, Mg (RPL) films from our previous study. The η HT, γ curves are consistent with Birks' law, where we observe expected quenching for increasing LET. Additionally, we present 2D RPL images, using a wedge phantom, from Al₂O₃:C, Mg films irradiated with proton and carbon beams, which resulted in a 2D depth dose distribution of the Bragg curve and a comparable LET dependence with the data obtained with the slabs. The results confirm that the images obtained can be advantageously applied to obtain dose distribution in proton and carbon therapy without many corrections. Highlights: Improved Al2 O3 :C, Mg films irradiated with charged particle beams. New luminescence efficiencies curves. Full 2D image along the Bragg curve acquired with wedge phantom.